Implications of glycerol metabolism for lipid production. (October 2017) - Xue, Lu-Lu; Chen, Hao-Hong; Jiang, Jian-Guo
Abstract: Triacylglycerol (TAG) is an important product in oil-producing organisms. Biosynthesis of TAG can be completed through either esterification of fatty acids to glycerol backbone, or through esterification of 2-monoacylglycerol. This review will focus on the former pathway in which two precursors, fatty acid and glycerol-3-phosphate (G3P), are required for TAG formation. Tremendous progress has been made about the enzymes or genes that regulate the biosynthetic pathway of TAG. However, much attention has been paid to the fatty acid provision and the esterification process, while the possible role of G3P is largely neglected. Glycerol is extensively studied on its usage as carbon source for value-added products, but the modification of glycerol metabolism, which is directly associated with G3P synthesis, is seldom recognized in lipid investigations. The relevance among glycerol metabolism, G3P synthesis and lipid production is described, and the role of G3P in glycerol metabolism and lipid production are discussed in detail with an emphasis on how G3P affects lipid production through the modulation of glycerol metabolism. Observations of lipid metabolic changes due to glycerol related disruption in mammals, plants, and microorganisms are introduced. Altering glycerol metabolism results in the changes of final lipid content. Possible regulatory mechanisms concerning the relationship between glycerol metabolism and lipid production are summarized.